Construction of Ni@polypyrrole nanochains/Ti3C2Tx ternary composites with excellent microwave absorption properties. (12th September 2022) - Dai, Bo; Dong, Feng; Yu, Jia; Feng, Shixuan; Wang, Haowen; Li, Tingxi; Ma, Mingliang; Ding, Jianxu; Ma, Yong
Abstract : Ni@PPy NCs/Ti3 C2 T x ternary composites are successfully fabricated by the combination of solvothermal method, hydrothermal method and vacuum-assisted filtration, showing the optimum RLmin of −62.61 dB at 6.82 GHz and 2.71 mm. Abstract : Electromagnetic radiation has been a special form of environmental pollution that has attracted widespread attention in the past few decades. Combining the advantages of one-dimensional (1D) materials forming conductive networks and two-dimensional (2D) materials possessing multiple reflections is an excellent research method for the development of electromagnetic wave (EW) absorbing materials. Herein, Ni@polypyrrole nanochains/Ti3 C2 T x (Ni@PPy NCs/Ti3 C2 T x, NiPM) ternary composites have been successfully prepared through the combined utilization of the solvothermal method, hydrothermal method and vacuum-assisted filtration. The ternary composites consisting of 1D core-shell Ni@PPy NCs (NiP) and 2D Ti3 C2 T x can effectively combine conductive loss, dielectric loss and magnetic loss, resulting in excellent impedance matching. The minimum reflection loss (RLmin ) of the prepared ternary composites can be up to −62.61 dB at 6.82 GHz with a thickness of 2.71 mm while the effective absorption bandwidth (EAB) is 4.46 GHz at 1.38 mm. This work provides a general guideline for the development of a MXene and conducting polymer matrix design for EW absorbing materials.